Solid-Phase Preparation of Al-TiO2 for Efficient Separation of Bioderived Product Danshensu. (3rd November 2019) - Chang, Fei; He, Zhong Bing; Zhou, Quan
Abstract : Four kinds of Al-TiO2 solid samples with different Ti/Al ratios of 1 : 0.1, 1 : 0.09, 1 : 0.07, and 1 : 0.05 were synthesized via a solid-phase synthesis method and characterized by XRD, SEM, EDS, BET, and other techniques. The prepared solids were used for separation of the bioderived product danshensu, the content of which was determined by UV spectrophotometry. Moreover, the effects of extract concentration, PH value, adsorption time, and ethanol elution volume were investigated. The results showed that these Al-TiO2 samples had good adsorption and desorption ability. Especially, the solid Al-TiO2 with a Ti/Al ratio of 1 : 0.05 is more suitable for the separation of danshensu, exhibiting a higher adsorption (77.70%) under 2 h adsorption time and pH = 3; meanwhile, the high desorption rate (70.29%）was received under 80% ethanol and the sample concentration of 3.0 mg/mL.